Maternal killer-cell immunoglobulin-like receptors and paternal human leukocyte antigen ligands in recurrent pregnancy loss cases in Turkey - TULUNAY VİRLAN, AYSIN (KOREAN SOC REPRODUCTIVE MEDICINE, 2020)
Objective: The survival of a semi-allogeneic fetus depends on several immunological mechanisms, and it has been suggested that recurrent pregnancy loss (RPL) could develop as a result of one or more immunological abnormalities. Methods: Compatibility between partners for human leukocyte antigen (HLA) genotypes and the relationships between maternal killer-cell immunoglobulin-like receptor (KIR) and paternal HLA-Bw4/Bw6 and HLA-C1/C2 supra-groups were investigated in 25 couples with RPL in comparison to healthy couples with children. HLA and KIR genotyping was performed using polymerase chain reaction with sequence-specific primers and/or sequence-specific oligonucleotides. Results: HLA class I incompatibility between partners, especially in HLA-B alleles, was more common in the RPL group (p=0.01). HLA-C2 homozygosity was more frequent in the male partners of RPL couples than in other groups (p=0.03). The KIR2DL5 gene frequency was significantly higher in both the female and male partners of RPL couples, whereas the KIR2DS3 gene frequency in male partners of RPL couples was significantly reduced (p=0.03). The presence of KIR2DL3 in women with RPL was correlated with the presence of HLA-C2 alleles in their spouses (p=0.03). Conclusion: Our data from a Turkish population suggest that male HLA-C2 homozygosity may play an important role in RPL. Additionally, an incidental match between male HLA-C2 and female HLA-C1 ligand KIR receptors might perturb the balance between activatory and inhibitory KIR-ligand interactions during pregnancy in couples affected by RPL. The roles of orphan KIR2DL5 and orphan KIR2DS3 in RPL remain obscure.
Keywords: HLA C2; Human leukocyte antigen; Killer-cell immunoglobulin-like receptor genotyping; KIR2DL5; KIR2DS3; Recurrent pregnancy loss; HLA-DQ ALLELES; SPONTANEOUS-ABORTION; NK CELLS; C GENES; KIR; MOLECULES; IMMUNOLOGY; COUPLES; BW4